2003
DOI: 10.1212/01.wnl.0000055931.66009.d3
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological findings in Sneddon’s syndrome

Abstract: The authors report the neuropathologic findings in a case of Sneddon's syndrome. There were multiple small, predominantly cortical, infarcts, with focal hyperplasia and fibrotic occlusion of arterial vessels in the superficial white matter, cortex, and leptomeninges. A very occasional arterial thrombus was seen. These findings suggest that Sneddon's syndrome is caused by a noninflammatory arteriopathy affecting superficial cerebral vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…In aplABnegative cases, some authors have suggested a primary inflammatory process [10]. In general, SS is thought to be due to a progressive occlusive, noninflammatory vasculopathy of the small and mediumsized arteries [5,9]. Based on the existing data it remains unclear if the vasculopathy of SS caused the aneurysmatic dilatation in our patient or if this finding was coincidental.…”
Section: Letter To the Editorsmentioning
confidence: 75%
“…In aplABnegative cases, some authors have suggested a primary inflammatory process [10]. In general, SS is thought to be due to a progressive occlusive, noninflammatory vasculopathy of the small and mediumsized arteries [5,9]. Based on the existing data it remains unclear if the vasculopathy of SS caused the aneurysmatic dilatation in our patient or if this finding was coincidental.…”
Section: Letter To the Editorsmentioning
confidence: 75%
“…1 The treatment of SS patients with stroke has always focused on the prevention of recurrent vascular events and future disability. Little, if any, has been published on the management of acute ischemic stroke in patients with SS, particularly the use of thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…1 The pathogenesis may relate to progressive noninflammatory thrombotic vasculopathy affecting mainly mediumand small-sized arteries in the brain and skin. 2 The etiology of SS is unclear; SS is primary in some patients, without a clear etiology, and in others it is secondary to an autoimmune disorder or a thrombophilic state.…”
Section: Introductionmentioning
confidence: 99%
“…Since its first description in 1965, Sneddon syndrome is defined as the association of livedo reticularis, ischemic cerebrovascular disease, heart valve disease, and renal failure in the absence of a recognized collagen-vascular disease or infection [1][2][3]. It is common in women between 20 and 42 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome may be differentiated according to the presence or absence of circulating antiphospholipid (aPL) antibodies or aPL-positive Sneddon syndrome and aPL-negative Sneddon syndrome [6]. Approximately 60% of patients with the disorder are hypertensive, 35% have circulating aPL antibodies, and 50% of patients develop mental retardation [2]. Because Sneddon syndrome is associated with various prothrombotic abnormalities [7][8][9][10] that require anticoagulant therapy such as heparin [11], low-molecular-weight heparin (LMWH) [12], or coumadin [13], these patients should be evaluated carefully before surgery.…”
Section: Introductionmentioning
confidence: 99%